Awal Waktu Shalat Telaah Fiqh dan Sains - Muhajir, Muhajir (MADINAH, 2020)
Prayer is an obligation for Muslims, therefore we must know when the time of entry and passage of prayer times must be known carefully and well, not until the time of entering prayer has done it, as a result the prayer will be in vain without reward. Because one of the requirements for the validity of prayer is to pray at the appointed time. The prayer service has been arranged in the verses of qauliyah, the Qur'an and explained also in the hadith of the Prophet. While the signs of that time are based on natural changes that occur (the verses of His qauniyah) in the form of the sun, moon, stars, occurring day and night and other celestial bodies. With the presence of these signs so that people think with His authority and give thanks for the blessings He gives by worshiping. Determining prayer times in a normal area is very easy to do, namely by knowing the matarari position and its changes. Dhuhr prayer starts from the sun slipping until the shadows are all the same or twice the length. Asr prayer starts from the shadow of something of the same length or shadow twice the length until the sun turns yellow. Maghrib prayer starts from the sunset until the loss of mega red. Isha prayer when the sun is 18 ° below the horizon. Fajr prayer when the sun is located 20 ° below the horizon. As for prayer in the polar regions or abnormal areas, namely: 1). The science of fiqh teaches that in such circumstances the person concerned, after waking up or regaining consciousness, is obliged to immediately carry out the evening prayer, after which the morning prayer will take place. 2). Prayer times in areas with latitude exceeding 45 ° North and South can use areas that have only 45 ° latitude and their longitude does not change. 3). For areas that do not experience loss of red mega, then to determine Isha and Subuh time based on the previous (season) time which can distinguish mega red when Maghrib and mega red during Fajr.